Differential response of maize hybrids to field infection with Aspergillus flavus and aflatoxin accumulation in the Chaco Semi-arid region of Argentina - Barontini, Javier Miguel; Alaniz Zanon, Maria Silvina; Druetta, Marcelo Alberto; Ruiz Posse, Agustina María; Torrico Ramallo, Ada Karina; Monge, María del Pilar; Candela, Raúl Esteban; Chulze, Sofía Noemí; Gimenez, Maria De La Paz (Elsevier, 2022)
Maize is affected by Aspergillus flavus and by the contamination of its kernels with aflatoxins, of which AFB1 is the most important. The Chaco Semi-arid is a region of Argentina in which the climate conditions increase this problem and due to the use of resistant cultivars is the best available tactic to reduce aflatoxin accumulation, we analyzed six hybrids against artificial inoculation with native aflatoxin-producing isolates of A. flavus. A multifactorial experiment was conducted in three complete randomized blocks, under Inoculated and Non- Inoculated treatment, in two locations and during two growing seasons, in which yield, kernel infection, and AFB1 accumulation (using HPLC) were evaluated. P2089VYHR was outstanding during 2018/19 with 11,089 kg ha􀀀 1, coinciding with the growing season with the highest rainfall and 4% decrease in yield (395 kg ha􀀀 1) was observed between treatments. No yield differences were observed in the hybrids between localities, or in the hybrid × treatment interaction. The level of infection by A. flavus showed differences between localities and growing seasons but not between hybrids. The Inoculated treatment registered kernel infections above 50%, while natural infection was 35% during 2019/20, associated with rainfall below crop requirements during the flowering period. The AFB1 accumulation analysis identified P2089VYHR and P1366VYHR without AFB1 accumulation. Yield correlated negatively with the percentage of kernel infection, but not with AFB1 accumulation, while a positive correlation was observed between these last two parameters. The pathogen causes a decrease in yield in the region and there are hybrids that are resistant to AFB1.